A Picture Guessing Game to Improve English Skill at Sdn Baruh 1 - Rohmah, Miftahur (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
One of the difficulties students often experience in learning English is reading and speaking. Reading and speaking are activities that occur every day both at school, at home or in public places. Students in Indonesia experience difficulties when understanding reading and speaking English, mainly due to a lack of practice, the small vocabulary they have, and the lack of knowledge about appropriate English reading comprehension strategies. To improve the English language skills of students at Baruh 1 Elementary School, namely in the form of a picture guessing game to improve English language skills at Baruh 1 Elementary School. The approach used in this study is a descriptive qualitative research approach. The results of this study can be concluded that 6 students were very receptive and able to use English, because previously they had taken English lessons outside of school. 2 students are still classified as moderate in using English, they still experience a little difficulty in learning English. but he can know a little vocabulary used in learning English. 2 students still do not accept to use English, because they are not fluent in reading and cannot even read, so they find it difficult to do learning, including learning English. One of the most important skills implemented through deployment is the guessing game. Researchers use games as a learning medium. The picture guessing game is an activity that makes us more relaxed and fun. Based on research results, the proportion of success is 75%. The English picture guessing game for SDN Baruh 1 students is suitable for use and needs to be developed by increasing the number of pictures and adding the number of other categories, so that it can increase vocabulary in English. with picture game media to improve English learning, students are more enthusiastic in learning English and can train students' vocabulary, how to speak, where students are more efficient and more confident.